Manufacturing method of zirconium phosphate silver-loaded modified polytetrafluoroethylene microporous membrane for resisting bacteria and inhibiting pollution and blockage
By using zirconium phosphate silver-carrying modification technology in polytetrafluoroethylene microporous membranes, the problem of membrane pore blockage is solved, and the effect of efficient filtration and low maintenance costs is achieved.
Patent Information
- Application Number
- CN202411955820.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
AI Technical Summary
Polytetrafluoroethylene microporous membranes are prone to pore blockage in high-polluted water quality environments, resulting in increased membrane resistance and reduced filtration efficiency.
Using the method of manufacturing a polytetrafluoroethylene microporous membrane modified with zirconium phosphate, a mixed solution of silane coupling agent and distilled water is prepared, and a zirconium phosphate nanopowder is added to uniformly adhere to the surface of the polytetrafluoroethylene suspended particles. After drying, blending, oil removal and stretching, a microporous membrane with improved mechanical properties and antibacterial effects is prepared.
It effectively avoids membrane pore blockage, maintains high water flux, reduces maintenance cycle and maintenance costs, and improves the filtration efficiency of the membrane.
Smart Images

Figure CN119701686A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polytetrafluoroethylene microporous membranes, and in particular relates to a method for manufacturing a polytetrafluoroethylene microporous membrane modified with silver-loaded zirconium phosphate for antibacterial and anti-fouling clogging. Background Art
[0002] Polytetrafluoroethylene, or PTFE, has excellent comprehensive properties such as high temperature resistance, corrosion resistance, non-stickiness, self-lubrication, excellent dielectric properties, and very low friction coefficient. The hollow fiber membrane made of it has the advantages of strong hydrophobicity, oxidation resistance, acid and alkali resistance, temperature resistance, and good biocompatibility. It is particularly suitable for microporous membrane filtration technology. As a key process in sewage treatment, its high-efficiency filtration and low-cost maintenance directly affect the direct interests of sewage treatment companies. Polytetrafluoroethylene microporous membrane has excellent chemical stability, small micropore diameter, and high filtration accuracy. However, in an environment with highly polluted water quality, the growing microbial slime will quickly adhere to the membrane surface, blocking the membrane pores, resulting in increased membrane resistance and reduced filtration efficiency.
[0003] The microstructure of zirconium phosphate silver antibacterial agent is layered crystal, which is similar to the layered structure of graphene, and can improve the mechanical properties of composite polytetrafluoroethylene microporous membrane. At the same time, zirconium phosphate silver antibacterial agent can release metal Ag+, which can quickly "kill" microorganisms attached to the surface of membrane pores, avoid clogging of membrane pores, maintain high water flux, reduce maintenance cycle, and reduce maintenance costs.
[0004] Therefore, there is an urgent need for a manufacturing process for applying the silver-loaded zirconium phosphate antibacterial agent to polytetrafluoroethylene microporous membranes. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a method for manufacturing a zirconium phosphate-supported silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling purposes, so as to avoid the problems of pore clogging, increased membrane resistance and low filtration efficiency of the previous polytetrafluoroethylene microporous membrane during filtration.
[0006] In order to solve the above technical problems, the present invention discloses a method for manufacturing a polytetrafluoroethylene microporous membrane modified with silver-loaded zirconium phosphate for antibacterial and anti-fouling clogging, which comprises: Step a. Prepare a 1%wt mixed solution of a silane coupling agent and distilled water, and then weigh 5%wt of zirconium phosphate silver nanopowder, add it to the mixed solution and stir to obtain a solution A; Step b. Take a commercially available polytetrafluoroethylene suspension as solution B, slowly add the prepared solution A to solution B, stir at a low speed for more than 30 minutes, and evenly attach the nano-scale zirconium phosphate silver to the surface of the polytetrafluoroethylene suspension particles to obtain solution C; Step c. Take an appropriate amount of ammonia water and slowly add it to solution C, and adjust the pH value to 9±0.5; the suspended particles of polytetrafluoroethylene modified with silver zirconium phosphate in the solution are precipitated from the solution; select a metal filter with a mesh size greater than 80, filter the suspended particles, and repeatedly wash them with distilled water for more than 3 times until the pH value of the washing solution is neutral; spread the suspended filtered particles evenly, place them in a temperature oven, set the temperature at 80°C-120°C, and dry them for more than 8 hours to obtain a mixture D; Step d. 18%-25%wt kerosene was blended and stirred with the mixture D, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene was evenly dispersed to obtain a mixture E; Step e. The mixture E is made into various outer diameter sizes of zirconium phosphate silver-modified polytetrafluoroethylene hollow tubes by using a pressing, extrusion equipment and process, and is placed at a temperature of 220°C-240°C for degreasing treatment; then, a stretching device is used to stretch it using the principle of "wheel speed difference" with a stretching ratio of 2-5 times; finally, the stretched microporous membrane is cured to improve its mechanical properties, the curing temperature is 350°C-370°C, and the curing speed is 9m / min-12m / min, thereby preparing a zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane.
[0007] According to one embodiment of the present invention, the silane coupling agent in the above step a is selected from at least one of KH550, KH560 or KH570; the addition of the silane coupling agent is conducive to dispersing the silver nanoparticles and improving the antibacterial effect.
[0008] According to one embodiment of the present invention, the nanopowder of silver-loaded zirconium phosphate in the above step a is a layered crystal structure with an average particle size of less than 100 nm, which is similar to the layered graphene structure and can improve the mechanical properties of the modified polytetrafluoroethylene microporous membrane.
[0009] According to one embodiment of the present invention, the weight ratio of the nano-powder of silver supported by zirconium phosphate in the above step a is in the range of 1%-5%.
[0010] According to one embodiment of the present invention, in the above step b, the mass fraction of solution A is selected from 1 part, and the mass fraction of solution B is selected from 10-25 parts.
[0011] Compared with the prior art, the present invention can achieve the following technical effects: The layered structure of zirconium phosphate-supported silver is similar to the structure of graphene and can improve the mechanical properties of polytetrafluoroethylene microporous membranes; Zirconium phosphate-loaded silver has excellent antibacterial properties and can quickly "kill" microbial slime attached to the surface of membrane pores, avoiding clogging of membrane pores and increased membrane resistance, maintaining high water flux, reducing maintenance cycles, reducing maintenance costs, and improving membrane filtration efficiency.
[0012] Of course, any product implementing the present invention does not necessarily need to achieve all of the above-mentioned technical effects at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 The microscopic morphology of the silver-supported zirconium phosphate modified polytetrafluoroethylene microporous membrane with a stretching ratio of 2.5 times; Figure 2 This is the microscopic morphology of the polytetrafluoroethylene microporous membrane modified with silver-loaded zirconium phosphate with a stretching ratio of 4.0 times. DETAILED DESCRIPTION
[0014] The following will describe the implementation methods of the present invention in detail with reference to the accompanying drawings and embodiments, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0015] The present invention discloses a method for manufacturing a polytetrafluoroethylene microporous membrane modified with silver-loaded zirconium phosphate for antibacterial and anti-fouling clogging, which comprises: Step a. Prepare a mixed solution of 1%wt of silane coupling agent and distilled water, then weigh 5%wt of zirconium phosphate silver nanopowder, add it to the mixed solution and stir evenly to obtain solution A; the silane coupling agent is selected from at least one of KH550, KH560 or KH570, and the addition of silane coupling agent is conducive to dispersing silver nanoparticles and improving the antibacterial effect; the zirconium phosphate silver nanopowder has a layered crystal structure, which is similar to the layered graphene structure, and the average particle size is less than 100nm, which can improve the mechanical properties of the modified polytetrafluoroethylene microporous membrane. Its addition weight ratio range is 1%-5%; Step b. Take a commercially available polytetrafluoroethylene suspension as solution B, slowly add the prepared solution A to solution B, stir at a low speed for more than 30 minutes, and evenly attach the nano-scale zirconium phosphate silver to the surface of the polytetrafluoroethylene suspension particles to obtain solution C; Step c. Take an appropriate amount of ammonia water and slowly add it to solution C, and adjust the pH value to 9±0.5; the suspended particles of polytetrafluoroethylene modified with silver zirconium phosphate in the solution are precipitated from the solution; select a metal filter with a mesh size greater than 80, filter the suspended particles, and repeatedly wash them with distilled water for more than 3 times until the pH value of the washing solution is neutral; spread the suspended filtered particles evenly, place them in a temperature oven, set the temperature at 80°C-120°C, and dry them for more than 8 hours to obtain a mixture D; Step d. 18%-25%wt kerosene was blended and stirred with the mixture D, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene was evenly dispersed to obtain a mixture E; Step e. The mixture E is made into various outer diameter sizes of zirconium phosphate silver-modified polytetrafluoroethylene hollow tubes by using a pressing, extrusion equipment and process, and is placed at a temperature of 220°C-240°C for degreasing treatment; then, a stretching device is used to stretch it using the principle of "wheel speed difference" with a stretching ratio of 2-5 times; finally, the stretched microporous membrane is cured to improve its mechanical properties, the curing temperature is 350°C-370°C, and the curing speed is 9m / min-12m / min, thereby preparing a zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane.
[0016] Implementation Case 1 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 25 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 1.0%wt phosphate silver-loaded nanopowder. A polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate; then 22%wt kerosene and the polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube; at a temperature of 220°C, the extruded hollow tube is deoiled and stretched at a ratio of 2.5 times to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, under the process parameters of a curing temperature of 362°C and a curing speed of 9.4m / min, the mechanical properties of the microporous membrane are improved.
[0017] Implementation Case 2 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 25 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 1.0%wt phosphate silver-loaded nanopowder. A polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate; then, 22%wt kerosene and the polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube; at a temperature of 220°C, the extruded hollow tube is deoiled and stretched at a ratio of 4.0 to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, under the process parameters of a curing temperature of 357°C and a curing speed of 11.0m / min, the mechanical properties of the microporous membrane are improved.
[0018] Implementation Case 3 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 12.5 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 2.0%wt phosphate A polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate; then, 22.5%wt kerosene and the polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube; at a temperature of 220°C, the extruded hollow tube is deoiled and stretched at a ratio of 2.5 times to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, under the process parameters of a curing temperature of 361°C and a curing speed of 9.4m / min, the mechanical properties of the microporous membrane are improved.
[0019] Implementation Case 4 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 12.5 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 2.0%wt phosphate A polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate; then, 22.5%wt kerosene and the polytetrafluoroethylene composite powder modified with silver-loaded zirconium phosphate are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube; at a temperature of 220°C, the extruded hollow tube is deoiled and stretched at a ratio of 4.0 to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, under the process parameters of a curing temperature of 356°C and a curing speed of 11.0m / min, the mechanical properties of the microporous membrane are improved.
[0020] Implementation Case 5 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 10 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 2.5%wt phosphoric acid Zirconium-supported silver-modified polytetrafluoroethylene composite powder; then 22.5%wt kerosene and zirconium phosphate-supported silver-modified polytetrafluoroethylene composite powder are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube, and the extruded hollow tube is deoiled at a temperature of 220°C, and is stretched at a ratio of 2.5 times to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, the mechanical properties of the microporous membrane are improved under the process parameters of a curing temperature of 361°C and a curing speed of 9.4m / min.
[0021] Implementation Case 6 According to the mass fraction, a mixed solution of 1%wt HK550 coupling agent and distilled water was prepared, and then 5%wt of zirconium phosphate silver-loaded nanopowder was weighed and added to the mixed solution and stirred evenly to prepare a zirconium phosphate silver-loaded homogeneous dispersion; then, according to the mass fraction, 1 part of the zirconium phosphate silver-loaded dispersion was slowly added to 10 parts of the polytetrafluoroethylene dispersion, stirred evenly, and ammonia water was added to adjust the pH value to about 9, so that the zirconium phosphate silver-loaded polytetrafluoroethylene suspended particles were precipitated from the solution, and the suspended filtered particles were evenly spread out and placed in an oven at a temperature of 80°C-120°C and dried for more than 8 hours to prepare a 2.5%wt phosphoric acid Zirconium-supported silver-modified polytetrafluoroethylene composite powder; then 22.5%wt kerosene and zirconium phosphate-supported silver-modified polytetrafluoroethylene composite powder are stirred at a low speed, and placed in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed, and the mixture is pressed and extruded to prepare a Φ2.8*Φ1.4 modified polytetrafluoroethylene hollow tube, and the extruded hollow tube is deoiled at a temperature of 220°C, and is stretched at a ratio of 4.0 to prepare a modified polytetrafluoroethylene hollow microporous membrane; finally, the mechanical properties of the microporous membrane are improved under the process parameters of a curing temperature of 357°C and a curing speed of 11.0m / min.
[0022] Please refer to the following Figure 1 and Figure 2 , Figure 1 The microscopic morphology of the silver-supported zirconium phosphate modified polytetrafluoroethylene microporous membrane with a stretching ratio of 2.5 times; Figure 2 The microscopic morphology of the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane with a stretching ratio of 4.0 times. In addition, the polytetrafluoroethylene microporous membranes modified with different contents of zirconium phosphate silver-modified prepared in Examples 1-6 and the conventional polytetrafluoroethylene microporous membranes on the market without zirconium phosphate silver-modified were subjected to a tensile test. At the same time, 10g of Examples 1-6 and the conventional polytetrafluoroethylene microporous membranes without zirconium phosphate silver-modified were weighed, washed and soaked in a Staphylococcus aureus suspension, and cultured in a 37°C incubator for 18h for a control test. The colony count was observed and the sterilization rate was calculated. The performance and experimental results are shown in the following table;
[0023] In summary, the 2%wt zirconium phosphate silver-modified polytetrafluoroethylene composite powder prepared in Example 3-4 has the highest tensile strength, whether it is stretched 2.5 times or 4.0 times. At the same time, zirconium phosphate silver can release metal Ag+, which can quickly "kill" microorganisms attached to the surface of membrane pores, and has a very high sterilization rate. At the same time, it avoids membrane pore blockage, maintains high water flux, reduces maintenance cycles, and reduces maintenance costs.
[0024] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for producing a polytetrafluoroethylene microporous membrane modified with silver-loaded zirconium phosphate for antibacterial and anti-fouling clogging, characterized in that: include: Step a. Prepare a 1%wt mixed solution of a silane coupling agent and distilled water, and then weigh 5%wt of zirconium phosphate silver nanopowder, add it to the mixed solution and stir to obtain a solution A; Step b. Take a commercially available polytetrafluoroethylene suspension as solution B, slowly add the prepared solution A to solution B, stir at a low speed for more than 30 minutes, and evenly attach the nano-scale zirconium phosphate silver to the surface of the polytetrafluoroethylene suspension particles to obtain solution C; Step c. Take an appropriate amount of ammonia water and slowly add it to solution C, and adjust the pH value to 9±0.5; the suspended particles of polytetrafluoroethylene modified with silver zirconium phosphate in the solution are precipitated from the solution; select a metal filter with a mesh size greater than 80, filter the suspended particles, and repeatedly wash them with distilled water for more than 3 times until the pH value of the washing solution is neutral; spread the suspended filtered particles evenly, place them in a temperature oven, set the temperature at 80°C-120°C, and dry them for more than 8 hours to obtain a mixture D; Step d. providing 18%-25%wt kerosene and the mixture D for blending and stirring, and placing in a 45°C oven for more than 12 hours to ensure that the kerosene is evenly dispersed to obtain a mixture E; Step e. The mixture E is made into various outer diameter sizes of zirconium phosphate silver-modified polytetrafluoroethylene hollow tubes by using a pressing, extrusion equipment and process, and is placed at a temperature of 220°C-240°C for degreasing treatment; then, it is stretched by using a stretching device and utilizing the principle of "wheel speed difference" with a stretching ratio of 2-5 times; finally, the stretched microporous membrane is cured to prepare a zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane.
2. The method for manufacturing the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling according to claim 1, characterized in that: The silane coupling agent in step a is selected from at least one of KH550, KH560 or KH570.
3. The method for producing the antibacterial and anti-fouling zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane according to claim 1, characterized in that: The nanometer powder of silver-loaded zirconium phosphate in step a has a layered crystal structure and an average particle size of less than 100 nm.
4. The method for producing the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling according to claim 1, characterized in that: The weight ratio of the nanometer powder of silver-loaded zirconium phosphate added in step a is in the range of 1% to 5%.
5. The method for manufacturing the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling according to claim 1, characterized in that: In the step b, the mass fraction of solution A is selected from 1 part, and the mass fraction of solution B is selected from 10-25 parts.
6. The method for manufacturing the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling according to claim 1, characterized in that: In the step e, the curing temperature is 350° C.-370° C., and the curing speed is 9 m / min-12 m / min.
7. The method for manufacturing the zirconium phosphate silver-modified polytetrafluoroethylene microporous membrane for antibacterial and anti-fouling according to claim 1, characterized in that: In the step e, 2.0%wt of zirconium phosphate silver-modified polytetrafluoroethylene composite powder is prepared.